Analysis of Financial and Non-Financial Annual Reports of Islamic Banks, Between Welfare State and Warfare State (Comparative Overlook at Bank of London and The Middles East, UK and Arab Islamic Bank, Palestine) - Khairul Fuady (Jurnal Penelitian Ekonomi Akuntansi, 2018)
This study aims to evaluate two IBs from two different countries i.e. Bank of London and the Middle East (BLME) in UK and Arab Islamic Bank in Palestine on how they perform the annual report. The evaluation will compare both financial and non-financial report of both annual report from three consecutive years from 2013 to 2015. Financial analysis employs financial parameters such as Eikon and Orbis while non financial analysis use diction and LWIC parameters and CSR standards of AAOIFI and Belal et al (2004). As a comparative approach, this study also includes data of World-wide Islamic banks in average for analysis of financial report. Despite operating in warfare state, AIB shows more distinctive nature of Islamic bank idealism in their financial report. It is indicated from the low rate of LLPs imposed during hurdle time of Palestine decreased economy growth. Meanwhile the opposite policy is employed by BLME as shown by aggressive LLPs in time of economy downward of UK following Brexit. In compliance with Islamic moral objectives such practices are not encouraged in Islam. This finding also confirms Abdelsalam, et.al., 2016 on how LLPs aggressively imposed are indicative of manipulation during negative economy circumstances. From the analysis of non-financial report this study prevails that as a bank operating in a warfare state, Arab Islamic Bank still try to strive the service for the community as their corporate responsibility. On the other hand BLME as a bank working in a welfare state and a developed country the annual reports provided do not show such corporate responsibility. Furthermore as an Islamic bank, BLME bears the ethical and social requirement to accomplish. Aside from CSR aspect, annual reports of AIB also outweigh BLME in performance of zakah and qard hasan as Islamic instruments in achieving the social justice of Islamic economy goals.